DYNAMICS OF CONTAMINATION OF WATERS OF AGRICULTURAL SETTING BY HEAVY METALS - Коваль, В. В.; Кучерявий, С. О.; Наталочка, В. О.; Нечитайло, В. М.; Фесенко, О. Г. (Scientific Progress & Innovations, 2014)
The research results of the salt content of heavy metals in natural waters of the Poltava region have been shown. It is emphasized that one of the pollutants of water sources is chemicalization of agriculture. The studies were conducted in 2008-2012 on the basis of the Poltava Regional State Technological Design Center to protect soil fertility and quality. The results of studies showed that overrunning of maximum permissible concentration is not observed, therefore, there are prerequisites for doing organic farming in the region. However, a prerequisite to this is the availability of objective information concerning the agro-ecological status of groundwater and water resources, as well as the introduction of environmentally friendly technologies of growing crops.